PENGARUH SENAM DISMENORE TERHADAP NYERI DISMENORE PADA REMAJA PUTRI - Domas Nurchandra Pramudianti (Jurnal Ilmu Kebidanan, 2022)
Dysmenorrhea is pain that occurs in the lower abdomen that is felt during menstruation and can be primary or secondary due to an increase in the hormone prostaglandin which causes the uterine muscles to contract. From the data obtained, about 50% of women experience dysmenorrhea during menstruation, which makes them unable to carry out daily activities for 1-3 days each month. This study aims to determine the effect of dysmenorrhea gymnastics on the reduction of menstrual pain. This study is a quasi-experimental study with a non-equivalent design with a control group (two groups pre-test-post-test). The population are 61 people, with a sample of 18 people taken by simple random sampling. Measuring tool to identify dysmenorrhea using a numerical scale. The treatment given was dysmenorrhea gymnastics 5 times in a row in a week before the female student was menstruating. The average pain scale before being given to the intervention group was 5.79 (moderate pain), in the control group was 5.30 (moderate pain), while the average pain scale after dysmenorrhoea exercise in the treatment group was 2.32 (mild pain) and 5.10 in the control group ( currently). Statistical test analysis using the Independent T-test obtained a p-value of 0.006 <α=0.05 indicating that there is a significant influence between gymnastics on the decline in menstrual pain. Dysmenorrhea exercise performed 5 times in a row during the week before menstruation can reduce menstrual pain in female students.